THE DEPENDENCE OF THE AFFECTIVE DISORDERS MANIFESTATION ON MORPHOFUNCTIONAL CONDITION OF THE BRAIN AFTER TRAUMATIC BRAIN INJURY - Hryn, K.V.; Hryn, V.H.; Fedorchenko, I.L.; Yushchenko, Yu.P. (World of Medicine and Biology, 2018)
The occurrence and degree of psychiatric disorders manifestation mainly depends on the morphofunctional state of the brain. Generally, the prevailing number of military personnel who took part in combat operations suffers from post traumatic stress disorder and sustained traumatic brain injury. The purpose of the present study was to determine the dependence of the affective disorders manifestation on the brain’s morphofunctional state after traumatic brain injury. Once the informed consents were collected, 60 patients, aged 19 to 60 years, who participated in the combat operations and suffered from non-psychotic psychiatric disorders and received in-patient treatment at one of the units of the O.F. Maltsev Poltava Regional Clinical Psychiatric Hospital during the period from 2014 to 2016 were examined. The performed studies’ results demonstrate that the manifestation degree of psychiatric disorders depends upon the morpho-functional condition of the brain. Patients with post-traumatic stress disorders and psychiatric disorders caused by the injured brain (due to craniocerebral injury) should receive the compulsory comprehensive psychotropic and vascular therapy.
Keywords: morpho-functional condition of the brain; craniocerebral injury; post traumatic stress disorder